Pengaruh Perbedaan Kedalaman Setting pada Alat Tangkap Pancing Ulur terhadap Hasil Tangkapan Ikan Madidihang (Thunnus Albacares) di Perairan Mentawai yang Didaratkan di Pelabuhan Perikanan Samudera Bungus - Achmad Fardianzah Nasution; M Tajuddin Noor; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
This research aims to analyze the effect of different setting depths of handline fishing gear on catches of yellowfin tuna (Thunnus albacares) in Mentawai waters which are landed at the Bungus Ocean Fishing Port. The research was carried out using field experimental methods at three setting depths, namely 25 meters, 50 meters and 75 meters. The research results show that a depth of 25 meters produces the most optimal catch compared to other depths. This depth has the advantages of abundant availability of target fish, optimal visibility, as well as temperatures and oxygen levels that support fish activity. Data were analyzed using analysis of variance (ANOVA) and Least Significant Difference test (LSD). The analysis results show that differences in depth have a very real influence (**). These findings provide practical guidance in optimizing fishing gear depth to increase catch yields sustainably.